Valuing the conservation of sea turtles in Brgy. Lawi, Jordan, Guimaras an application of discrete choice experiment method. - Aborka, Rio Rina B.
To increase the population and remove the endangered status of sea turtles in Brgy. Lawi, Jordan, Guimaras, an effective and sustainable conservation program is a must. Using discrete choice experiment valuation method, this study determined the residents? preferred conservation scheme for sea turtles in Brgy. Lawi and estimated the conservation value for these creatures. A total enumeration of 204 residents was employed in the study. Improvements in listing status and the establishment of conservation facilities were the identified attributes of conserving sea turtles in the area. Results show that the establishment of conservation facilities with souvenir shop attribute level was mostly preferred. Income and age significantly affect the choice of the residents for improvements in a conservation scheme. Also, results show that the residents have positive attitudes towards conserving sea turtles and are willing to pay for it. The inclusion of an eco-tourism scheme, such as the addition of a souvenir shop that would open opportunities and generate income while still promoting the protection and conservation of sea turtles in the area, is thus recommended. For further studies, the research recommended to include more attributes that could capture a wider scope of characteristic from the resource or good being valued.